ANALISIS PUBLIC TRUST DALAM LAYANAN BUS TRANSJAKARTA KHUSUS PEREMPUAN PADA RUTE 1 BLOK M-KOTA - Sabrina Aurellia Putri; Endang Larasati Setianingsih (Journal of Management and Public Policy, 2026)
The Transjakarta bus service has the highest number of users, but the lowest frequency of trips, compared to other modes of public transportation. This condition increases the risk of sexual harassment for women, who are the majority of Transjakarta users, thereby disrupting their safety and comfort. The provision of women-only areas on regular buses is considered suboptimal due to its limitations in preventing verbal and visual sexual harassment. In response, PT Transjakarta provides a women-only bus service on route 1, which is the most congested corridor. However, the limited number of buses and the lack of transparency in information have led to non-compliance by male users with the service rules, which negatively impacts the experience of female users. This study aims to analyze public trust and the factors that hinder the improvement of public trust in the Transjakarta women-only bus service on route 1. The research method used is qualitative with a descriptive approach. The results show that public trust is still weak because it has not been fully established in the dimensions of benevolence, competence, and fairness, while the dimension of credible commitment and honesty shows a positive perception. Barriers to increasing public trust include responsiveness, reliability, integrity, and openness. Therefore, PT Transjakarta should increase the number of fleets, adjust service designs, and improve public information transparency to strengthen public trust in the women-only bus service.